2019
DOI: 10.1200/po.18.00343
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Longitudinal ctDNA Workflow Reveals Clinically Actionable Alterations in Ovarian Cancer

Abstract: PURPOSE Circulating tumor DNA (ctDNA) detection is a minimally invasive technique that offers dynamic molecular snapshots of genomic alterations in cancer. Although ctDNA markers can be used for early detection of cancers or for monitoring treatment efficacy, the value of ctDNA in guiding treatment decisions in solid cancers is controversial. Here, we monitored ctDNA to detect clinically actionable alterations during treatment of high-grade serous ovarian cancer, the most common and aggressive form of epitheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 34 publications
0
39
0
Order By: Relevance
“…We recently published a paper on the use of ctDNA in management of high-grade serous ovarian cancer (HGSOC) 2 . HGSOC is the most frequent and lethal subtype of epithelial ovarian cancer with five-year survival of only 43%.…”
mentioning
confidence: 99%
“…We recently published a paper on the use of ctDNA in management of high-grade serous ovarian cancer (HGSOC) 2 . HGSOC is the most frequent and lethal subtype of epithelial ovarian cancer with five-year survival of only 43%.…”
mentioning
confidence: 99%
“…One chemo resistant patient therapy has changed based on the detection of ERBB2 amplification and ctDNA-guided decision. These results can be considered as a proof of using ctDNA concept to guide the clinical decisions during the cycles of chemotherapy in ovarian cancers [118]. In addition, Noguchi et al [119] compared the variant allele frequency (VAF) of the measured ctDNA mutations during neoadjuvant chemotherapy in 10 plasma samples.…”
Section: Egf Receptormentioning
confidence: 86%
“…Some studies reported 68-100% concordance of mutations detected in plasma and tumor tissues. 10,11,43 Our gene panel sequencing method differed vastly to the number of genes examined by the abovementioned researchers. Phallen et al 10 analyzed 58 genes in various cancers, Oikkonen et al 11 investigated over 500 genes in ovarian cancer patients with different NGS approaches and Kim et al 43 examined genetic changes in only one gene using different mutation analysis.…”
Section: Discussionmentioning
confidence: 99%
“…10,11,43 Our gene panel sequencing method differed vastly to the number of genes examined by the abovementioned researchers. Phallen et al 10 analyzed 58 genes in various cancers, Oikkonen et al 11 investigated over 500 genes in ovarian cancer patients with different NGS approaches and Kim et al 43 examined genetic changes in only one gene using different mutation analysis. In contrast, other NGS analysis of BRCA1/2 mutations in ovarian cancer demonstrated 100% concordance between the tumor and ctDNA germline variants, but this was not observed in the case of somatic variants, indicating the intratumor heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation